Eco-friendly fabricated nonporous carbon nanofibers with high volumetric capacitance: improving rate performance by tri-dopants of nitrogen, phosphorus, and silicon. Issue 12 (26th October 2017) - Yang, Yuwei; Hou, Xueyuan; Ding, Chenfeng; Lan, Jin-Le; Yu, Yunhua; Yang, Xiaoping
Abstract : High rate performance of nonporous carbon nanofibers achieved via tri-dopants of nitrogen, phosphorus, and silicon. Abstract : Development of high volumetric capacitance, high rate performance and low-cost electrode materials for supercapacitors is still a significant challenge. Among the various promising candidates, carbon nanofibers (CNFs) with heteroatom functionalization have attracted increasing attention. Herein, a type of nonporous CNFs combined with a heteroatom functionalization strategy is proposed for high performance supercapacitor electrodes. Tri-heteroatom functionalization of nonporous carbon nanofibers was carried out by tetraethyl orthosilicate (TEOS) and phosphorus (H3 PO4 ) activation of polyacrylonitrile (PAN) through electrospinning and subsequent thermal treatment. The optimal electrode material showed a high gravimetric capacitance of 243.7 F g −1 at 0.5 A g −1, superior rate capability with ∼83% retention at rates ranging from 0.5 A g −1 to 30 A g −1 and excellent cycle stability (capacitance retention rate >100% after 8000 cycles at a high current density of 30 A g −1 ). It is worth noting that the nonporous CNF also possesses a high packing density, which presents a maximum volumetric capacitance of 253.4 F cm −3 at 0.5 A g −1 and 209 F cm −3 at 30 A g −1 . The current synthetic strategy of preparing nonporous carbon architectures with multi-heteroatom doping offers an eco-friendly, feasible, and cost-effective way for constructing high-performance electrode materials employed in supercapacitors.